Interprofessional education toolkit : practical strategies for program design, implementation, and assessment - Noureddine, Nassrine; Hagge, Darla; Ofstad, William (Plural Publishing Inc., 2022)
"Interprofessional education (IPE) and collaborative practice (IPCP) are the keys to improving health, safety, satisfaction and cost in the modern healthcare system. This IPE Toolkit provides healthcare educators, administrators, and clinicians with a practical, evidence-based manual for leading change. With these keys, we invite you to unlock meaningful collaboration for the next generation of health professionals, supported by an interprofessional collaboration of authors with more than 50 years of combined experience in education, practice, and scholarship in medicine, nursing, pharmacy, physical therapy, speech-language pathology, instructional design, simulation and online education"--